Chemical Constituents of the Essential Oil of Zosimia absinthifolia (Vent.) Link - A Shafaghat (Institue of Medicinal Plants, ACECR, 2007)
Background: The genus Zosimia is one of Umbelliferae family, widely distributed in different world regions, and have important essential oils. This genus is represented in Iran by two species: Z. radians Boiss. & Hohen. and Z. absinthifolia (Vent.) Link, which Z. radians is endemic plant. Objective: Investigation and identification of essential oil compositions of Zosimia absinthifolia collected from Khalkhal area Method: Water - distilled essential oil from the aerial parts of Zosimia absinthifolia (Vent.) Link, collected from Khalkhal area in June 2004, analyzed by GC and GC/MS. Results: Among the 21 identified components constituting 96% of the oil, Octyl acetate (24.69%), β - Caryophyllene (22.24%), and (Z) - β- Ocimen (8.9%) were found to be the major constituents. Conclusion: In the essential oil of the plant, sesquiterpenes predominated over monoterpenes.